Beyond Risk and Protective Factors: An Adaptation-Based Approach to Resilience. (July 2017) - Ellis, Bruce J.; Bianchi, JeanMarie; Griskevicius, Vladas; Frankenhuis, Willem E.
How does repeated or chronic childhood adversity shape social and cognitive abilities? According to the prevailing deficit model, children from high-stress backgrounds are at risk for impairments in learning and behavior, and the intervention goal is to prevent, reduce, or repair the damage. Missing from this deficit approach is an attempt to leverage the unique strengths and abilities that develop in response to high-stress environments. Evolutionary-developmental models emphasize the coherent, functional changes that occur in response to stress over the life course. Research in birds, rodents, and humans suggests that developmental exposures to stress can improve forms of attention, perception, learning, memory, and problem solving that are ecologically relevant in harsh-unpredictable environments (as per the specialization hypothesis ). Many of these skills and abilities, moreover, are primarily manifest in currently stressful contexts where they would provide the greatest fitness-relevant advantages (as per the sensitization hypothesis ). This perspective supports an alternative adaptation-based approach to resilience that converges on a central question: "What are the attention, learning, memory, problem-solving, and decision-making strategies that are enhanced through exposures to childhood adversity?" At an applied level, this approach focuses on how we can work with, rather than against, these strengths to promote success in education, employment, and civic life.